Artificial Soft Elastic Media with Periodic Hard Inclusions for Tailoring Strain‐Sensitive Thin‐Film Responses. Issue 40 (21st August 2018) - Byun, Junghwan; Chung, Seungjun; Hong, Yongtaek
Abstract: Engineering the coupling behavior between a functional thin film and a soft substrate provides an attractive pathway for controlling various properties of thin‐film materials. However, existing studies mostly rely on uniform deformation of the substrate, and the effect of well‐regulated and nonuniform strain distributions on strain‐sensitive thin‐film responses still remains elusive. Herein, artificially strain‐regulated elastic media are presented as a novel platform for tailoring strain‐sensitive thin‐film responses. The proposed artificial soft elastic media are composed of embedded arrays of inkjet‐printed polymeric strain modulators that exhibit a high modulus contrast with respect to that of the soft matrix. This strain‐modulating lattice induces spatially regulated strain distributions based on localized strain‐coupling. Controlling the structural parameters and lattice configurations of the media leads to spatial modulation of the microscopically localized as well as macroscopically accumulated strain profiles. Uniform thin films coupled to these media undergo artificially tailored deformation through lattice‐like strain‐coupled pathways. The resulting phenomena yield programmable strain‐sensitive responses such as spatial arrangement of ternary‐state surface wrinkles and stepwise tuning of piezoresistive responses. This work will open a new avenue for addressing the issue of controlling strain‐sensitive thin‐film properties through structural engineering of artificial soft elastic media. Abstract : Artificial soft elastic media composed of inkjet‐printed polymeric microlattices are developed as a novel platform for tailoring the microscopic morphological and macroscopic piezoresistive responses of coupled thin films. Based on the ability to modulate lattice‐like strain‐coupling, the proposed concept shows that controlling strain‐sensitive thin‐film properties can be achieved by engineering the structural parameters of the soft elastic media.